Sporadic hereditary neuropathies misdiagnosed as chronic inflammatory demyelinating polyradiculoneuropathy: Pitfalls and red flags. Issue 1 (14th January 2020) - Campagnolo, Marta; Taioli, Federica; Cacciavillani, Mario; Ruiz, Marta; Luigetti, Marco; Salvalaggio, Alessandro; Castellani, Francesca; Testi, Silvia; Ferrarini, Moreno; Cavallaro, Tiziana; Gasparotti, Roberto; Fabrizi, Gian Maria; et al.
Abstract: Hereditary neuropathies may be misdiagnosed with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). A correct diagnosis is crucial for avoiding unnecessary therapies and access genetic counseling. We report on nine patients (seven men, mean age 49.2 ± 16.1) diagnosed with and treated as CIDP, in whom mutations or variants of unknown significance (VUS) in genes associated with hereditary neuropathies were reported. All underwent neurological and neurophysiological examination, eight also cerebrospinal fluid (CSF) analysis. In 4/9, nerve ultrasound and/or MR‐neurography were performed. All the patients complained of progressive upper or lower limbs sensory‐motor symptoms, with heterogeneous disease duration (1‐34 years, mean 8.6 ± 10.8). Neurophysiology showed demyelinating signs in seven patients, mixed findings with predominant axonal damage in two patients. Neuroimaging disclosed diffuse abnormalities at proximal and distal segments. Molecular screening showed PMP22 duplication in two patients, mutations in the MPZ, EGR2, and GJB1 genes were reported in each of the remaining patients. The two patients with mixed neurophysiological findings had p.Val30Met mutation in the transthyretin gene. Two patients had VUS in the MARS and HSPB1 genes. Four patients had partial response to immunomodulant therapies, and CSF and neurophysiological features suggesting an inflammatory condition concomitant with the hereditary neuropathy. Hereditary neuropathy may be misdiagnosed with CIDP. The most common pitfalls are CSF (high protein levels and oligoclonal bands), incorrect interpretation of neurophysiology, and transient benefit from therapies. Neuroimaging may be helpful in cases with atypical presentations or when severe axonal damage complicate the neurophysiological interpretation.